(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we use the Chaundy-Bullard combinatorial identity to prove some identities involving the Pochhammer k-symbol. In fact, these contribution generalize the results given in the paper [O. Kouba, A Chaundy-Bullard type identity involving the Pochhammer symbol, J. Indagationes Mathematicae 34 (2023) 186-189; Available online at https://doi.org/10.1016/j.indag.2022.10.009]. We also give some Chaundy-Bullard type identity verified by the generalized hypergeometric series.